Skandinavien som imago i det ungarske litterære tidsskrift Nyugat (1907/1908–1941): En kritisk læsning af nogle nationale stereotyper og deres efterliv - Csúr, Gábor Attila (Scandinavistica Vilnensis, 2023)
My study focuses on how national stereotypes characterized the interpretation of Scandinavian literature in the first half of the 20th century in Hungary. In these decades, translation from Danish, Norwegian and Swedish became increasingly intensive, and, thanks to a handful of enthusiastic translators, authors associated with the Modern Breakthrough movement and other late 19th-century tendencies achieved widespread popularity in Hungary. In the analysis I take a closer look at several reviews, translations and essays published in the literary journal Nyugat (1907/1908–1941) where a lot of later prominent Hungarian authors and translators of the period started their career. The imago of Scandinavia created by these authors consists of climatic, anthropological, geographical, political and aesthetic elements. This mythical, distorted and stereotypical image of the Nordic countries exists even today, side by side with a critical reevaluation which actively shapes the academic milieu and the public cultural sphere.
Keywords: Working-class literature; Stig Sjödin; literature and politics; literature and memory; Folke Fridell; Jenny Wrangborg; Kurt Salomonson